Keanekaragaman Tumbuhan Pewarna Alami dan Pola Pemanfaatannya oleh Masyarakat Suku Aceh - Hartono, Adi; Sulaiman, Nanda Fahira; Arifah, Annisyah; Fauziani, Fauziani (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
The use of plants as natural dyes represents important traditional knowledge of the Acehnese people, closely linked to cultural practices, crafts, and the use of local natural resources. However, modernization and synthetic dyes threaten the continuity of these traditions. This study aimed to examine the diversity of natural dye plants and their utilization patterns within Acehnese communities. A qualitative ethnobotanical approach was applied through field observations, semi-structured interviews with key informants, and documentation of dye-producing plant species. Data were analyzed descriptively by grouping plants based on parts used, colors produced, and forms of utilization. The findings show that various local plant species are used as natural dye sources, with leaves, bark, and fruits being the most commonly utilized parts. Utilization patterns are strongly connected to cultural needs and local wisdom in maintaining environmental balance. The study concludes that ethnobotanical knowledge of natural dyes persists despite modernization, highlighting its importance for preserving local knowledge and promoting environmentally friendly dye alternatives in cultural and applied science contexts.